(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2024)
In the history of Eastern literature, as a result of the integration of fiction with religious-mystical concepts, that is, as a result of the influence of the Holy Qur’an and hadith, there are works of various genres that reflect universal ideas and moral concepts.